Development Strategy of Indonesian Palm Oil Industrial Cluster Based International Trade Connectivity - Raharja, Sapta; Djohar, Setiadi; Aryanthi, Dwi (International Journal of Oil Palm, 2021)
Indonesia is the largest producer and the exporter of palm oil in the world which has three palm oil industrial cluster (POIC) areas that are Sei Mangkei (North Sumatera), Dumai (Riau), and Maloy (East Kalimantan). To carry out the delivery of palm oil products to the destination countries, the Palm oil from the three POICs must be transshipment in Malaysia and Singapore. In line with this issues, a strategy to develop the POIC based international connectivity need to be done. This study aims to identify the actual conditions of POIC Indonesia, to determine the factors (internal and external) that influence the development of POIC, and to formulate priority strategy for developing POIC Indonesia. These are needed so that Indonesia can become a hub port of international trade especially in Asia. This research uses "Diamonds" Porter’s Model, gap analysis, and the Analytical Hierarchy Process (AHP). Based on the analysis connectivity, the main strategy that can be formulated in order to develop Indonesian palm oil industry cluster is infrastructure improvements. This strategy can be done if the government (the Ministry of economy, Ministry of industry and trade, Ministry of sea, PT PELINDO, and local government), private sector, academic, and the public is able to work together and integrated.